Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1038/s41564-021-00878-z
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule imaging reveals that Z-ring condensation is essential for cell division in Bacillus subtilis

Abstract: How proteins in the bacterial cell division complex (the divisome) coordinate to divide bacteria remains unknown. To explore how these proteins collectively function, we conducted a complete dynamic characterization of the proteins involved, and then examined the function of FtsZ binding proteins (ZBPs) and their role in cytokinesis. We find that the divisome consists of two dynamically distinct subcomplexes: stationary ZBPs that transiently bind to treadmilling FtsZ filaments, and a directionally-moving compl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
52
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 62 publications
6
52
2
Order By: Relevance
“…It is different from the tight bundles caused by divalent ions, which will greatly reduce the activity of FtsZ GTPase and slow down their dynamics ( Yu and Margolin, 1997 ; Mukherjee and Lutkenhaus, 1999 ; Chen and Erickson, 2009 ). Recent research discovered that ZapA does not affect the FtsZ treadmilling rate in vivo and in vitro and suggested the dynamics of FtsZ polymers in vivo may be intrinsic to the polymer itself ( Caldas et al, 2019 ; Walker et al, 2020 ; Squyres et al, 2021 ). The double filament formed by FtsZ-ZapAL also has a loose structure; the gap between two FtsZ filaments is about 3 nm.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is different from the tight bundles caused by divalent ions, which will greatly reduce the activity of FtsZ GTPase and slow down their dynamics ( Yu and Margolin, 1997 ; Mukherjee and Lutkenhaus, 1999 ; Chen and Erickson, 2009 ). Recent research discovered that ZapA does not affect the FtsZ treadmilling rate in vivo and in vitro and suggested the dynamics of FtsZ polymers in vivo may be intrinsic to the polymer itself ( Caldas et al, 2019 ; Walker et al, 2020 ; Squyres et al, 2021 ). The double filament formed by FtsZ-ZapAL also has a loose structure; the gap between two FtsZ filaments is about 3 nm.…”
Section: Discussionmentioning
confidence: 99%
“…In B. subtilis , previous studies showed that FtsZ binding proteins contain ZapA, SepF, and EzrA, and knockout of zapA or sepF gene alone did not alter cell morphology, but when ezrA is knocked out together, the cell displays severe division impairment ( Gueiros-Filho and Losick, 2002 ). Squyres et al (2021) suggested that FtsZ binding proteins bundle FtsZ filaments into a condensed Z-ring, which is important to recruit downstream proteins, including cell wall synthesis enzymes to the division site. Without FtsZ-binding proteins, ZapA and EzrA, Z-ring condensation disappears.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations